The transition from linear to-parabolic growth of Cu3Si phase in Cu/a-Si system. (May 2018) - Parditka, Bence; Zaka, Hanaa; Erdélyi, Gábor; Langer, Gábor A.; Ibrahim, Mohammed; Schmitz, Guido; Balogh-Michels, Zoltán; Erdélyi, Zoltán
Abstract: The solid state reaction between Cu and a-Si films was investigated at 150–200 °C by depth profiling with secondary neutral mass spectrometry. Intermixing was observed leading to the formation of a homogeneous Cu3 Si layer at the interface. The growth of the crystalline silicide follows a parabolic law at 165 °C and 200 °C. At 150 °C a transition from linear to parabolic kinetics is observed. Combining with our previous experimental results showing linear kinetics at 135 °C [Acta Materialia, 61 (2013) 7173–7179], the temperature dependence of the linear and parabolic coefficients as well as the transition length can be estimated. Graphical abstract: Unlabelled Image